Enhancing tourist experiences through a web based scavenger hunt: a case study of Kota Bharu’s self guided tour system / Arinah Izzati Mohd Afazi … [et al.] - Mohd Afazi, Arinah Izzati; Che Fauzi, Ainul Azila; Mat, Asiah; Fauzi, Auni; Md Nasir, Syerina Azlin; Mohamad Arifin, Mohamad Syauqi (Unit Penerbitan UiTM Kelantan, 2024)
The tourism industry is a thriving sector globally, contributing significantly to economic growth and employment opportunities. Beyond the financial benefits, tourism enables individuals to immerse themselves in diverse cultures, languages, and histories, fostering cross-cultural understanding and enriching experiences. However, tourists often encounter challenges such as limited facilities and ineffective marketing strategies, which can hinder their overall travel experiences. To address these issues and enhance tourist experience, this study focuses on the development of a web-based system known as the Kota Bharu Self-Guided Scavenger Hunt and Tour. Following the System Development Life Cycle (SDLC) methodology, specifically the waterfall model, this project aims to create an interactive and engaging platform for tourists. The web-based system offers a range of features designed to facilitate seamless exploration and enjoyment of tourist attractions. Users can easily access information about popular destinations, historical sites, cultural landmarks, and other points of interest. The system incorporates Google Maps integration, providing guided directions to ensure visitors easy navigation. Additionally, the platform allows users to upload photos, manage store and owner profiles, and access lists of players, store owners, stores, and checkpoints. By leveraging these functionalities, tourists can select specific categories of interest and embark on an exciting scavenger hunt adventure. Looking ahead, one future recommendation for further system enhancement is the exploration of a mobile application. Developing a mobile app would offer greater accessibility and convenience, allowing users to access the scavenger hunt and tour features directly from their smartphones. This would enable on-the-go access to information, navigation, and real-time updates, enhancing the overall user experience.